Integrasi Prinsip Pengadaan Berkelanjutan dalam Proyek Konstruksi Publik di Indonesia - Nasution, Soraya Muthma Innah (Universitas Quality, 2025)
The construction industry significantly contributes to global resource consumption and environmental degradation, positioning it as a key sector in achieving the Sustainable Development Goals (SDGs). Its high usage of materials, water, and energy, alongside substantial carbon emissions, underscores its critical role in sustainable development efforts. Therefore, integrating sustainability principles into construction projects is both urgent and potentially beneficial from a social perspective. Within this context, sustainable procurement emerges as a vital mechanism to enhance resource efficiency, generate socio-economic value, and safeguard labor rights across the supply chain. This study explores the implementation of sustainable procurement in public construction projects in Indonesia. Using six key principles outlined in ISO 20400—Organizational Policy and Strategy, Integration in Procurement Processes, Supply Chain Management, Operational Practices, Stakeholder Engagement, and Monitoring and Evaluation Systems—the research assesses adoption levels through a questionnaire distributed to government procurement practitioners in the construction sector. Results indicate a positive trend, with average implementation levels above 70%. The highest scores were found in Organizational Policy and Strategy and Supply Chain Management (84%), while Operational Practices lagged behind at 70%.Kata Kunci: Berkelanjutan; Implementasi; Indikator; Konstruksi Publik; Pengadaan